Menggugat Keberanian: Tindak Pidana Kekerasan Dalam Rumah Tangga dalam Tinjauan Yuridis - Darlia, Darlia; Asba, Patahillah; Saputra, Iswandy Rani (Jurnal Litigasi Amsir, 2024)
This study aims to analyze the Judge’s Legal Considerations in Decision Number: 89/Pid.Sus/2021/PN.Sdr and the application of the Material Criminal Law in the case. This study uses normative law research methods, which focus on theoretical analysis and deductive logic. The results of the study show that the application of criminal law to domestic violence by husbands against wives is in accordance with Pasal 44 Ayat (1) Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga. The judge considers the fulfillment of the elements in the article based on the facts revealed during the trial. The defendant was sentenced to five months in prison and was required to pay a case fee of five thousand rupiah. In making a decision, the judge considers the prosecutor’s demands, evidence, testimony, and aggravating and mitigating circumstances, without any justifying reason to acquit the defendant of guilt.